Analysis of cut orientation through half-finished product using WEDM. Issue 1 (2nd January 2019) - Mouralova, K.; Benes, L.; Zahradnicek, R.; Bednar, J.; Hrabec, P.; Prokes, T.; Hrdy, R.
ABSTRACT: Wire electrical discharge machining (WEDM) is a non-traditional technology utilized to manufacture parts of complex shapes or machining the materials conventionally difficult to process. It is also applied in the aerospace industry, where Inconel 625, which was the subject of the research in this study based on aDesign of experiment (DoE), is usually machined. In this way, the experiment contained 33 rounds during which the settings of machined parameters were changed systematically. An identical experiment (33 rounds) was performed in which the semi-finished product was rotated by 90° to define the impact of the orientation direction of the cut on the speed of cutting and the quality of the surface and subsurface layers. Subsequently, a complex analysis of the machined surfaces of the individual samples was performed, including both the surface and subsurface layers. Topography was evaluated using a non-contact profilometer, including the creation of a color-filtered 3D surface relief. The subject of further investigation was the analysis of morphology and surface defects including the chemical composition analysis. For a very detailed observation of the distribution of the individual elements in the material, lamella was prepared, which was subsequently studied using a Transmission Electron Microscope (TEM). For the subsurface layer study and its defects, metallographic preparations of all samples, which were observed using both light and electron microscopy, were prepared. On the basis of the analyses performed, the impact of the cutting direction on the cutting speed as well as the machined surface quality was determined.